The miraculous summer. Francesco Salfi and the Jacobin offensive to the Marian miracles of 1796 (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
After the arrival of Napoleon in Italy, in 1796, extraordinary events occurred all over the peninsula: sacred images, especially Marian images, began, according to many testimonies, moving the eyes, blinking, raising up arms. What came to be known as the “miraculous wave” is a well-known event; the Jacobin reaction to the phenomenon, on the other hand, is less well studied. For the most radical patriots, it was not just a problem of public order, but an obstacle to the acceptance of the new Republic. Articles against the authenticity of the phenomenon appeared in some newspapers of the time, with Francesco Salfi’s Saggio di fenomeni antropologici (1783-84) as a reference point. A text that has several links with the articles written against the miracles during the 1796, and that allows to identify Salfi as the author of some of them.
Keywords: miracles; Salfi; Italian Jacobins; journals; earthquake; superstition